Peran Kurikulum Merdeka Pada Pembelajaran Ipas Kelas 6 SD Negeri 1 Bareng Lor - Rosyid Khoirul Nafian; Muhammad Akbar Nur Rohmat; Defita Berliani Putri; Diah Ayu Sekar Ningrum; Rofiana Prilia Anisa; Fauziyyah Muna Kharomah; Sri Suwartini (Jurnal Pendidikan Sosial Dan Konseling, 2024)
The role of the curriculum is to implement curriculum programs that have been developed in the previous stage, then tested with implementation and management, as it is carried out adjustment to the field situation and characteristics of students, including their intellectual, emotional and physical development. The results of this research are the implementation of the Independent Curriculum, Learning Planning, Learning Implementation, and School and Teacher Efforts in Implementing the Independent Curriculum at SD Negeri 1 Barenglor. The method used in this research is a qualitative method in this method. (Sugiyono, 2020) stated that "qualitative methods are artistic methods because the process is less patterned and is classified as a method because the data is in conjunction with data collected in the field".